$(a-b)^2 \,=\, a^2+b^2-2ab$

Let’s take two literals $a$ and $b$, and assume that they denote two quantities in algebraic form.

- Firstly, subtract the literal $b$ from $a$ but it is not possible because the values of them are unknown. However, their difference is mathematically written as a binomial $a-b$.
- Now, the square of the binomial $a$ minus $b$ is expressed as $(a-b)^2$ in mathematics.

The expression $(a-b)^2$ is basically an algebraic expression, and we usually read it in the following two ways in mathematics.

- The $a$ minus $b$ whole square.
- The square of $a$ minus $b$.

Let’s learn what $a$ minus $b$ whole square is from its expansion.

$(a-b)^2 \,=\, a^2-2ab+b^2$

$a$ minus $b$ whole square is expanded as $a$ square minus two times the product of $a$ and $b$ plus $b$ square.

Let’s take $a = 3$ and $b = 1$.

Now, find the value of expression $(a-b)^2$ by substituting the values of $a$ and $b$.

$\implies$ $(3-1)^2$ $\,=\,$ $(2)^2$ $\,=\,$ $4$

Similarly, evaluate the expression $a^2-2ab+b^2$ by substituting the values of $a$ and $b$.

$\implies$ $3^2-2(3)(1)+1^2$ $\,=\,$ $9-6+1$ $\,=\,$ $4$

Now, compare the values of both sides of the algebraic equation to verify their equality numerically.

$\,\,\,\therefore\,\,\,\,\,\,$ $(3-1)^2$ $\,=\,$ $4$ $\,=\,$ $3^2-2(3)(1)+1^2$

The square of $a-b$ is true for all the values of $a$ and $b$. It is defined in algebraic form. Hence, the $a$ minus $b$ whole square is generally called an algebraic identity and it can be used as a formula in mathematics.

The $a-b$ whole square identity is mainly used in two different cases in mathematics.

$\implies$ $(a-b)^2 \,=\, a^2+b^2-2ab$

$\implies$ $a^2+b^2-2ab \,=\, (a-b)^2$

Let us learn how to use the formula of $a$ minus $b$ whole square from the following simple examples.

$(1) \,\,\,$ Expand $(2x-5y)^2$

Take $a = 2x$ and $b = 5y$, and replace them in the expansion of the formula for calculating the value in mathematical form.

$\implies$ $(2x-5y)^2$ $\,=\,$ $(2x)^2+(5y)^2-2(2x)(5y)$

$\implies$ $(2x-5y)^2$ $\,=\,$ $4x^2+25y^2-2 \times 2x \times 5y$

$\,\,\, \therefore \,\,\,\,\,\,$ $(2x-5y)^2$ $\,=\,$ $4x^2+25y^2-20xy$

$(2) \,\,\,$ Simplify $9m^2+16n^2-24mn$

$\implies$ $9m^2+16n^2-24mn$ $\,=\,$ $(3m)^2+(4n)^2-24mn$

$\implies$ $9m^2+16n^2-24mn$ $\,=\,$ $(3m)^2+(4n)^2-2 \times 3 \times 4 \times m \times n$

$\implies$ $9m^2+16n^2-24mn$ $\,=\,$ $(3m)^2+(4n)^2-2 \times 3 \times m \times 4 \times n$

$\implies$ $9m^2+16n^2-24mn$ $\,=\,$ $(3m)^2+(4n)^2-2 \times (3m) \times (4n)$

$\implies$ $9m^2+16n^2-24mn$ $\,=\,$ $(3m)^2+(4n)^2-2(3m)(4n)$

Take $a = 3m$ and $b = 4n$. Now, simplify the algebraic expression by the $(a-b)^2$ algebraic identity

$\,\,\, \therefore \,\,\,\,\,\,$ $9m^2+16n^2-24mn$ $\,=\,$ $(3m-4n)^2$

The formula of square of $a-b$ can be derived mathematically in two distinct methods.

Learn how to derive the $a-b$ whole square identity by multiplying the binomials.

Learn how to prove the $a-b$ whole squared formula by the areas of geometric shapes.

Latest Math Topics

Jul 20, 2023

Jun 26, 2023

Jun 23, 2023

Latest Math Problems

Jul 01, 2023

Jun 25, 2023

Copyright © 2012 - 2023 Math Doubts, All Rights Reserved